2013
DOI: 10.1111/joa.12132
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the caudal zona incerta in rodents and primates

Abstract: SummaryThe caudal zona incerta is the target of a recent modification of established procedures for deep brain stimulation (DBS) for Parkinson's disease and tremor. The caudal zona incerta contains a number of neuronal populations that are distinct in terms of their cytoarchitecture, connections, and pattern of immunomarkers and is located at a position where a number of major tracts converge before turning toward their final destination in the forebrain. However, it is not clear which of the anatomical featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 53 publications
1
54
1
Order By: Relevance
“…Controlling the spread of virus transduction is difficult, and in fact in our LH study we Lateral hypothalamus GABA and reward consumption M Navarro et al observed strong virus transduction in GABAergic neurons in both the LH and ZI. Similar to the LH, much of the ZI is comprised of a dense population of GABAergic neurons (Watson et al, 2014). Although little is known about the functional role of the ZI, the subthalamus region, which includes the ZI, has been implicated in modulating consumption of natural and drug rewards (Lardeux et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the spread of virus transduction is difficult, and in fact in our LH study we Lateral hypothalamus GABA and reward consumption M Navarro et al observed strong virus transduction in GABAergic neurons in both the LH and ZI. Similar to the LH, much of the ZI is comprised of a dense population of GABAergic neurons (Watson et al, 2014). Although little is known about the functional role of the ZI, the subthalamus region, which includes the ZI, has been implicated in modulating consumption of natural and drug rewards (Lardeux et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The area posterior to the STN that includes the cZI is referred to as the posterior subthalamic area. Differences between the rostral and caudal portions are evident in projections as well as cell type [17, 18]. The region surrounding the ZI (including the caudal and rostral portions) includes 3 main structures involved in motor control: the cerebellothalamic tract, prelemniscal radiation, and the pallidothalamic tract [17-19].…”
Section: Discussionmentioning
confidence: 99%
“…The most knowledge about the ZI anatomy and physiology comes from studies in rodents, however, their results only partly can be compared with those obtained in some other species and humans [65,66]. The ZI in rats extends from rostral regions of the thalamus to the rostral pole of the red nucleus [66,67] and in humans from the rostral regions of the thalamus to the level of the rostral pole of the medial geniculate nucleus [66]. The ZI has been divided in rats into 4 main sectors: rostral, dorsal, ventral and caudal [66,67], although borders between them are not clear [68].…”
Section: Anatomy Of the Zi: Chemoarchitecture And Connectionsmentioning
confidence: 99%